Social accounting and its contribution to society - Vigante, Inese; Sneidere, Ruta (Buhalterinės apskaitos teorija ir praktika, 2013)
With the development of the society and its economic system, a need has emerged to develop accounting as well. The increasing role of social accounting, which keeps records of for-profit, non-profit, and governmental organisations, is associated with the complexity of the environment in which businesses and organisations are operating and presenting reports about their social, ethical, and environmental aspects. Organisations are subject to greater transparency, and many stakeholders are interested in and concerned about the performance of organisations within the context that is not reflected, to a satisfactory extent, in traditional accounting. Traditional accounting ensures reporting to the shareholders or the state, whereas social accounting provides information to all stakeholders, including the public. Social accounting includes all kinds of accounts that go beyond the economic and for all the different labels under which it appears. This paper deals with the main issues and tools of corporate social responsibility, which is a very important prerequisite for organisations in order to introduce the principles of social accounting.
Keywords: social accounting; transparency; corporate social responsibility